Effect of pH and agitation on growth of bacillus subtilis - Noorhisham Tan Kofli; Mohd. Sahaid Kalil (Universiti Kebangsaan Malaysia, 1999)
The effect of initial pH of medium (6.0,6.5 and 7.2) and agitation (100,200 and 300 rpm) on growth of oxygen sensitive culture of Bacillus subtilis were studied using shake flask cultures. Two type of media used were complex medium (CM) and well defined medium (WDM3). The effect of both parameters and types of media on production of acetoin and 2,3-butanediol were also studied. The maximum growth was detected in experiment with agitation at 300 rpm and pH 6.5 for both CM (2.87 g/l dry weight) and WDM3 (3.33 g/l dry weight). The use of WDM3 gave higher total products (acetoin+butanediol) concentration (0.67 g/l) compare to CM (0.44 g/l)